Rola sprawozdań finansowych w procesie podejmowania decyzji w przedsiębiorstwie - Maruszczak, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The article presents legal aspects of making financial statements. Indicates required features and defines which of them are most essential from the point of view of decision makers in an economic operator. The article also draws attention to an issue of control and examination of financial statements by expert auditors and regional chambers of auditors. It touches the subject of controlling in an enterprise as well as location of financial statement in enterprise financial analysis. It presents also the scope of information that must be shown by various economic operators in their financial statements. The article points on a balance sheet, a profit and loss account and a cash flow statement as indispensable elements in decision making process in an economic operator. It draws a special attention to a cash flow statement as a basis for making decisions and a main source of information in a small enterprise.
Keywords: rachunek zysków i strat; sprawozdanie finansowe; rachunek przepływów pieniężnych; controller; bilans